Conservation tillage facilitates the accumulation of soil organic carbon fractions by affecting the microbial community in an eolian sandy soil - Li, Yu-mei; Wang, Yu-ming; Qiu, Guang-wei; Yu, Hong-jiu; Liu, Feng-man; Wang, Gen-lin; Duan, Yan (Frontiers in Microbiology, 2024)
Conservation tillage (CT) is an important agronomic measure that facilitates soil organic carbon (SOC) accumulation by reducing soil disturbance and plant residue mulching, thus increasing crop yields, improving soil fertility and achieving C neutrality. However, our understanding of the microbial mechanism underlying SOC fraction accumulation under different tillage practices is still lacking. Here, a 6-year in situ field experiment was carried out to explore the effects of CT and traditional tillage (CK) practices on SOC fractions in an aeolian sandy soil. Compared with CK, CT increased the particulate OC (POC) content in the 0-30 cm soil layer and the mineral-associated OC (MAOC) content in the 0-20 cm soil layer. Moreover, tillage type and soil depth had significant influences on the bacterial, fungal and protistan community compositions and structures. The co-occurrence network was divided into 4 ecological modules, and module 1 exhibited significant correlations with the POC and MOC contents. After determining their topological roles, we identified the keystone taxa in the network. The results indicated that the most common bacterial taxa may result in SOC loss due to low C use efficiency, while specific fungal (Cephalotrichum) and protistan (Cercozoa) species could facilitate SOC fraction accumulation by promoting macroaggregate formation and predation. Therefore, the increase in keystone fungi and protists, as well as the reduction in bacteria, drove module 1 community function, which in turn promoted SOC sequestration under CT. These results strengthen our understanding of microbial functions in the accrual of SOC fractions, which contributes to the development of conservation agriculture on the Northeast China Plain.